What Theological Explanation Could and Could Not Be - Bishop, John Christopher (European journal for philosophy of religion, 2018)
The worldview of theism proposes an ultimate and global explanation of existence itself. What could such "theological explanation" possibly amount to? I shall consider what is unsatisfactory about a widely accepted answer-namely that existence is to be explained as produced and sustained by a supernatural personal agent of unsurpassably great power and goodness. I will suggest an alternative way in which existence could be open to a genuinely ultimate explanation, namely in terms of its being inherently directed upon a supremely good end or telos and existing just because that telos is concretely realized. On this "euteleological" view, theological explanation, though it may need to be compatible with our best scientific theoretical explanations, operates in a clearly distinct explanatory dimension.